World Cinema between the rock of the unknowable and the hard place of the as yet unknown. Issue 1 (2nd January 2021) - Stone, Rob; Freijo, Luis
ABSTRACT: Hypotheses that instigated the possibility of destabilising and de-westernising film theory have inspired a critical framework for analysing World Cinema that demands new and evolving understandings of its construction and fluidity, particularly in relation to its lost pasts and possible futures. Referencing several key works in this field and responding to David Martin-Jones's Cinema Against Doublethink: Ethical Encounters with the Lost Pasts of World History (2019) in particular, this article questions what is unknowable and as yet unknown about World Cinema. Following Derrida, it argues that the answers lie in how World Cinema gains meaning(s) through the process of différance (difference and deferral of meaning), particularly through genre. Deploying and dismantling genre theory in case studies of Wind River (Sheridan 2017), Chung Hing sam la/Chungking Express (Wong 1994 ), Faa yeung nin wa/In The Mood for Love (Wong 2000), Moonlight (Jenkins 2016) and Widows (McQueen 2018), the article targets the logjam of ethical hesitancy in approaching World Cinema and, holding that impurities in western cinema constitute trace evidence of new paradigms happening elsewhere in World Cinema, posits empathy and its deferral as essential to an understanding of the dynamics of the cinemas of the world.